Trade Linkages and the Globalisation of Inflation in Asia and the Pacific - Raphael A. Auer; Aaron Mehrotra (Center for Economic Studies and ifo Institute (CESifo), 2014)
Some observers argue that increased real integration has led to greater co-movement of prices internationally. We examine the evidence for cross-border price spillovers among economies participating in the pan-Asian cross-border production networks. Starting with country-level data, we find that both producer price and consumer price inflation rates move more closely together between those Asian economies that trade more with one another, ie that share a higher degree of trade intensity. Next, using a novel data set based on the World Input-Output Database (WIOD), we examine the importance of the supply chain for cross-border price spillovers at the sectoral level. We document the increasing importance of imported intermediate inputs for economies in the Asia-Pacific region and examine the impact on domestic producer prices of changes in costs of imported intermediate inputs. Our results suggest that real integration through the supply chain matters for domestic price dynamics in the Asia-Pacific region.
Keywords: E31; F40; F14; F15; F62; 330; globalisation; inflation; Asian manufacturing supply chain; price spillovers